Human Attitudes to Nature in Four Stories from The Decameron 2020 - Sumpor, Svjetlana (Poznańskie Studia Slawistyczne, 2022)
The Decameron 2020 started in Croatia as an online literary event in the time of the first quarantine caused by the Covid-19 pandemic and resulted in an e-book of fifty-two selected short stories. Its initiators and editors, Ana Cerovac, Vesna Kurilić and Antonija Mežnarić, recognized the peculiarity of the experience of living in the end times, as well as the potential for comparison of the e-book with Boccaccio’s classic, and set up an online space where authors from Croatia and the region could ( re )create or transform their experiences, or reflect upon them. This paper focuses on four stories from the collection in which nature is given special significance: Algernonova osveta (Algernon’s Revenge) by Nataša Milić, Zaražena (Infected) bySunčica Mamula, Redukcije(Reductions) byAnaKutleša and 2030 byRadmila Rakas. It investigates the range of feelings and attitudes towards nature in the time of pandemic and quarantine, as reflected in these four stories.